Earth's magnetosphere formed by the low-latitude boundary layer - Heikkila, Walter J (Elsevier, 2011)
The author argues that, after four decades of debate about the interaction of solar wind with the magnetosphere, it is time to get back to basics. Starting with Newton's law, this book also examines Maxwell's equations and subsidiary equations such as continuity, constitutive relations and the Lorentz transformation, Helmholtz' theorem, and Poynting's theorem, among other methods for understanding this interaction. Includes chapters on prompt particle acceleration to high energies, plasma transfer event, and the low latitude boundary layer. More than 200 figures illustrate the text, which includes a color insert.